Removal of Dissolved Reactive Red Dye from Aqueous Solution by Coconut Coir Carbon - ABDUL KARIM, NASHRUL IZZUAN (Universiti Teknologi Petronas, 2008)
Previous studies have proved that industrial effluents, especially reactive dyes have been one of the major pollutants to the enviromnent. This paper consists of the progress and development of using coconut coir carbon as the remover material for the reactive dyes in aqueous solution. The main objective of the study is to produce a low cost adsorbent from readily available material to remove dissolved reactive red dye from aqueous solution by adsorption, using the coconut coir carbon as well as to evaluate the effectiveness of the method such as finding the optimum condition for removal of reactive red dye by studying the effect of contact time, pH, initial concentration of the reactive red, and temperature on the reactive red adsorption process. The adsorbent was the coconut coir carbon. The activated carbon was prepared by crushing the coconut coir to finer particles, treated with sulphuric acid HzS04 and kept into an air oven with I 05°C temperature for 24 hours. Several test for the studies were done to prove and determine the effectiveness of the method such as dye adsorption studies and regeneration studies. The study is divided into two stages. The first stage involving literature reviews and background studies and the stage 2 by laboratory test, final report and results presentation. The exact completion of the study is within a year; completion of stage 1 in first half of the year and stage 2 in second half of the year.